Hungarian Monitoring, 23 April 1989 . [Magyar rádiófigyelő], 1989. április 23 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - 47 arrested in Moscow for taking part in unauthorized opposition meeting - Chronicle of events in Poland - Latest series of tragedies in Beirut Domestic Affairs: - Károly Grósz speaks to Japanese TV on uncovering events of 1956 - Alliance of Democratic Youth (DEMISZ) first national session continues - Historians register protest against composition of Show Trials Investigative Committee - Sándor Harangi's recollections of conscripts' Soviet captivity Economy: - Hungarian Socialist Workers' Party (MSZMP) general secretary: dynamic structural change in the economy will require 5 years and USD 2.5 billion of investment - Chamber of Commerce assists 105 Hungarian companies to find American partners for cooperation Külpolitika: - Moszkvában 47 embert letartóztattak mert nem engedélyezett ellenzéki gyűlésen vettek részt - Lengyelországi esemény-krónika - Az újabb bejrúti tragédia-sorozat Belpolitika: - Grósz Károly a japán TV-nek nyilatkozott az 56-os események feltárásával kapcsolatosan - Folytatódott a DEMISZ első országos ülése - Máris tiltakozást jelentettek be a történészek a Koncepciós Pereket Felülvizsgáló Bizottság összetétele ellen - Harangi Sándor visszaemlékezései a sorkatonák szovjet hadifogságáról Gazdaság: - Az MSZMP főtitkára szerint a gazdaság dinamikus szerkezetváltásához öt év alatt mintegy 2 és félmilliárd dollárnyi összeget kellene beruházni - A Gazdasági Kamara közvetítésével 105 magyar vállalat keres együttműködésre amerikai partnereket